Utilization of high-fidelity simulation to address challenges with the basic science immunology education of preclinical medical students - Cavuoto Petrizzo, Marie; Barilla-LaBarca, Maria-Louise; Lim, Youn Seon; Jongco, Artemio M.; Cassara, Michael; Anglim, James; Stern, Joel N.H. (BMC medical education, 2019)
Background Immune function and dysfunction are highly complex basic science concepts introduced in the preclinical medical school curriculum. A challenge for early learners is connecting the intricate details and concepts in immunology with clinical manifestations. This impedes relevance and applicability. The impetus in medical education reform is promoting consolidation of basic science and clinical medicine during the first two years of medical school. Simulation is an innovation now widely employed in medical schools to enhance clinical learning. Its use in basic science curriculums is largely deficient. The authors piloted simulation as a novel curricular approach to enhance fundamental immunology knowledge and clinical integration. Methods The authors introduced a Primary Immunodeficiency Disease (PIDD) simulation during a basic science immunology course for second-year medical students at the Zucker School of Medicine at Hofstra/Northwell. The simulation tasked small groups of students with evaluating, diagnosing and managing an infant with previously undiagnosed immunodeficiency. Joint facilitation by clinical and science faculty during terminal debriefings engaged students in Socratic discussion. Debriefing aimed to immerse basic science content in the context of the clinical case. Students completed a post-simulation Likert survey, assessing utility in reinforcing clinical reasoning, integration of basic science and clinical immunology, enhanced knowledge and understanding of immunodeficiency, and enhanced learning. A summative Immunodeficiency Objective Structured Clinical Examination (OSCE) question was created by faculty to assess students’ recognition of a PIDD and clinical reasoning. Results The simulation was well received by students with > 90% endorsing each of the objectives on the post-simulation survey. The authors also determined a statistically significant score variance on the summative OSCE question. Higher scores were achieved by the cohort of students completing the OSCE post-simulation versus the cohort completing the OSCE pre-simulation. Conclusions The innovative use of simulation in a highly complex basic science immunology course provides relevance and consolidation for preclinical learners. Additional data will be collected to continuously assess application of concepts and proficiency stemming from this novel curricular intervention. The authors advocate the initiation and/or expansion of simulation in non-clinical basic science courses such as immunology to bridge the gap between theory and practice.